Effects of Alternative Fish Species Amblypharyngodon Mola for Traditional Carp Polyculture in Nepal - Karn, Basant Kumar; Gupta, Ranjana; Rai, Sunila (Journal of Institute of Science and Technology, 2018)
To increase the maximum productivity is prime aim in fish aquaculture from past few years. The increase in maximum standing crop of a pond depends upon the wider range of available foods in ecological niches from the selection of complementary species growing together. The present work was conducted in an attempt to identify the suitable fish species combinations among Hypophthalmichthys molitrix, Aristichthys nobilis, Ctenopharyngodon idella, Cyprinus carpio with the introduction of Amblypharyngodon mola in the prevalent method of fish polyculture system practiced in Nepal. The experiment was conducted for 120 days, in twelve 100 m2 earthen ponds which comprised the initial growing period of fish. As control, one pond was stocked with a species ratio usually employed in the country; H. molitrix (35 %), A. nobilis (10 %), L. rohita (15 %), C. mrigala (10 %), C. idella, (5 %) and C. carpio (25 %). Treatment 2 was stocked with the H. molitrix, A. nobilis, L. rohita and C. mrigala. Treatment 3 was stocked with the H. molitrix, A. nobilis, L. rohita, C. mrigala and C. idella and Treatment 4 was stocked with the H. molitrix, A. nobilis, L. rohita, C. mrigala and C. idella and C. carpio. Each treatment had three replicates. Carp fishes were stocked with stocking density 15000 ha -1 in all treatments. A. mola was stocked @ 50000 ha-1 in treatments, 2, 3 and 4. No significant correlation was found between the growth rate of fish species and the water quality parameters. The final weight of different species, in different treatments, showed statistical differences. Considering growth parameters, the best result was obtained in treatment 2. A complete exclusion of the A. mola in treatment 1 had no advantage over the other treatments; however, the combination of Hypophthalmichthys molitrix, Aristichthys nobilis, Labeo rohita and Cirrhinus mrigala allowed the introduction of A. mola, with positive effects. In addition, the introduction of A. mola in the polycultures tested had no effect over the other carp species. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 92-102